Pengaruh Keselamatan Kerja, Sistem Kerja, Dan Motivasi Kerja Terhadap Kinerja Karyawan Di Toko Jaya Raya Showroom Cabang Imam Bonjol - Putu Mas Sri Wahyuni; I Putu Agus Adnyana (Journal of Economic, Bussines and Accounting (COSTING), 2022)
This study aims to determine the effect of work safety, work systems and work motivation on employee performance at the Jaya Raya Store Showroom, Imam Bonjol Branch. The questionnaire technique method (questionnaire data collection) was used in this study. The data used can be calculated directly as numbers or variables and the data that can be measured is a type of quantitative data. In this study, there were 40 employees of Toko Jaya Raya Showroom, Imam Bonjol Branch as a sample. The data analysis method applied is the multiple linear analysis method using SPSS 18.0 tools. The results of the research obtained in this study are: 1. The work safety variable (X1) has a positive and significant influence, 2. The work system variable (X2) has a positive and insignificant effect, 3. The work motivation variable (X3) has a positive and significant impact. positive and significant impact on employee performance at Toko Jaya Raya Showroom Imam Bonjol Branch. Keywords: work safety, work system, work motivation, and employee performance